Innovation Capability As a Strategic Asset: Examining the Human Resource Dynamics and Technology Integration in Business Performance - Muh. Rasbi; Erwin Erwin; Andika Isma; Hajar Dewantara; Muhammad Nur Alam Muhajir (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to analyze business performance models using innovation capabilities, which are rarely used to improve business performance. Design/methodology/approach – The research method used is quantitative, collecting data from entrepreneurs using questionnaires and analyzing them using Partial Least Squares-Structural Equation Modeling Finding/Results – The findings of this study indicate that there is no significant relationship between innovation capabilities and business performance, and there is no moderating effect of technology access on the relationship between innovation capabilities and business performance. Originality/Value – This study contributes to the literature by uncovering a 'performance paradox', where innovation capability—contrary to conventional theories—shows no significant impact on business performance. It shifts the academic focus from internal innovation processes to the critical necessity of direct technology access as a primary driver for business resilience in the digital era.